Juridical Review Of The Granting Of Remissions To Prisoners Of Criminal Acts Of Corruption - Rizki Karina Azilia (Institute Of computer Science (IOCS), 2021)
Corruption has occurred systematically and widely, causing state financial losses, as well as violating the social and economic rights of the community at large. The most common punishment imposed on perpetrators of corruption is imprisonment. Law Number 12 of 1999 concerning Corrections states that one of the rights of prisoners is to obtain a reduction in their criminal period or remission, not least for prisoners who are perpetrators of corruption. The government has issued Government Regulation Number 28 of 2006 concerning the Terms and Procedures for the Implementation of the Rights of Correctional Inmates. Convicts of criminal acts of corruption can be given remission if they meet the requirements of good behavior and have served 1/3 (one third) of their criminal period. The study was conducted to find out the things that became the basis for granting remissions to prisoners, including convicts who were perpetrators of criminal acts of corruption and to find out how the legal arrangements for granting remissions to prisoners who were perpetrators of corruption in positive law in Indonesia. The type of research is normative juridical research. The data was collected through a literature study, and the data obtained were processed using qualitative data processing methods. This qualitative analysis is then linked to relevant problems and theories so that the data obtained are descriptive. The results of the analysis show that the correctional system seeks to realize the social reintegration of prisoners in prison, therefore the basis for granting remissions to prisoners is to motivate prisoners to behave well and accelerate prisoners who are well behaved so that they can be released and return to society before the actual date of freedom. The legal rules for granting remissions to convicts who commit corruption crimes are Government Regulation Number 28 of 2006, but have not been equipped with implementing regulations. The government should immediately provide clarity to this regulation by issuing implementing regulations so as to provide legal certainty for the Directorate General of Corrections.